Forest biomass-to-biofuel factory location problem with multiple objectives considering environmental uncertainties and social enterprises - Lin, Chun-Cheng; Kang, Jia-Rong; Huang, Guan-Lin; Liu, Wan-Yu (Journal of cleaner production, 2020)
Forest biomass energy enjoys merit of large production, renewability, and clean combustion. However, most related works focused on only the objective of minimization of cost or pollution, but seldom on the social aspect. Social enterprise provides business models that cope with social or environmental problems, e.g., offering employment opportunities in disadvantaged areas. Therefore, this work considers social enterprises and environmental uncertainties in a forest biomass-to-biofuel factory location problem with multiple objectives, which determines whether to open forest biomass-to-biofuel factories at their potential locations to meet the energy demand and other practical constraints. Aside from minimization of cost and carbon emissions, the concerned problem additionally considers the objective of maximizing the job offers provided by opening factories from the social enterprise aspect. Additionally, based on the fuzzy theory, this problem includes the following environmental uncertainties: uncertain number of inventory days, uncertain job offers per unit of surplus factory scale, uncertain biomass production amount, and uncertain biofuel demand due to the price fluctuation of fossil fuels. This work employs the GIS to determine candidate locations of acquiring forest biomass and opening factories, and then solves the problem by fuzzy multi-objective linear programming. Through simulation, we observe the conflict among objectives, compare the differences between the proposed method and previous methods, and analyze the key factors that affect practical implementation. Simulation results show that when the total biofuel demand exceeds 200 million liters per year, the proposed method provides 16% more job offers than the previous method that focused on only cost minimization. •The first model for multiple-objective forest biomass-to-biofuel facility location.•Objectives include job opportunities (from social enterprise), cost, and pollution.•Under uncertainties on inventory days, jobs per scale, production & demand amount.•Employ GIS and fuzzy multi-objective linear programming to address the problem.•Simulation shows tradeoff among objectives; sensitively analysis shows key factors.